2016
DOI: 10.1038/srep36372
|View full text |Cite
|
Sign up to set email alerts
|

Scanning of selection signature provides a glimpse into important economic traits in goats (Capra hircus)

Abstract: Goats (Capra hircus) are one of the oldest livestock domesticated species, and have been used for their milk, meat, hair and skins over much of the world. Detection of selection footprints in genomic regions can provide potential insights for understanding the genetic mechanism of specific phenotypic traits and better guide in animal breeding. The study presented here has generated 192.747G raw data and identified more than 5.03 million single-nucleotide polymorphisms (SNPs) and 334,151 Indels (insertions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 42 publications
10
34
0
Order By: Relevance
“…2c, Additional file 4: TableS4). And the ratio of transition and transversion was 3:1, which is similar to the previous studies [48].…”
Section: Identification Of Ase Snps In the F1 Hybrids Of Texel And Kasupporting
confidence: 91%
“…2c, Additional file 4: TableS4). And the ratio of transition and transversion was 3:1, which is similar to the previous studies [48].…”
Section: Identification Of Ase Snps In the F1 Hybrids Of Texel And Kasupporting
confidence: 91%
“…PRKAA1, protein kinase AMPactivated catalytic subunit alpha 1, served as an energy sensor that maintains energy homeostasis (Kahn et al, 2005;Krishan et al, 2014). And another gene, PARD3B with lower selection intensity here, had been identified with goat productive traits in another report (Guan et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…Besides, there were few association analysis of single gene, for example, the SNPs of POU class 1 homeobox 1 (POU1F1) and KISS1 genes, insertion/deletion (indel) variants of lysine demethylase 6A (KDM6A) and β-Type platelet-derived growth factor receptor (PDGFRB), and transcript variants of catenin beta 1 (CTNNB1) had been reported to be associated with goat LS trait (An et al, 2013;Cui et al, 2018;Zhang X. et al, 2018;Yang et al, 2019;Zhu et al, 2019). Meanwhile, the genome-wide research on goat is also very lacking, only fewer reports showed some novel mutation sites affecting goat reproduction by whole-genome sequence (Guan et al, 2016;Lai et al, 2016). According to Guan et al (2016), the reproductionrelated genes regard to neurohypophysial hormone activity, including PAIP2B, CCDC64, and EPB41L5, had been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding reproductive traits, using selection tests in pigs, previous studies demonstrated some strong selective signals belonging to the TGF-β signaling pathway (18,19). In addition, in goats, the genes regulating seasonal reproduction and litter size have been speci cally selected (20,21). Moreover, some fecundity-related genes revealed a strong selection signature in sheep from Ethiopia and Europe (22,23).…”
mentioning
confidence: 99%